In Defence of Psychiatric Diagnoses - Fellowes, Sam.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
(3z(BIn Defence of Psychiatric Diagnoses has the great virtues of being really clear and really interesting. Sam Fellowes lucidly sets out some fundamental issues in the philosophy of science and uses them to illuminate contested issues in psychiatric nosology. Philosophers, clinicians and mental health researchers can all learn a lot from this, and find new ways to talk to each other.(3y $1 (BDominic Murphy, Professor of Philosophy, University of Sydney, author of Psychiatry in the Scientific Image (2006) (3z(BIn this thought-provoking book, Sam Fellowes attempts to undermine many influential criticisms of contemporary psychiatric diagnoses by undermining the assumptions about the nature of science on which they rest. He defends, instead, a neo-Kantian view of science as a whole, which highlights the role of construction and idealisation rather than a simple mirroring of the natural world. The result is both a detailed scholarly defence of neo-Kantian philosophy of science and a timely intervention in discussions of psychiatric classification.(3y $1 (BTim Thornton, Emeritus Professor of Philosophy and Mental Health, University of Central Lancashire, author of Essential Philosophy of Psychiatry (2007) This open access book makes a distinctive contribution by providing a novel defence of psychiatric diagnoses. It defends psychiatric diagnoses by portraying them as idealised models understood in a neo-Kantian sense. It reject accounts which see psychiatric diagnoses as biomedical entities or as natural kinds. Drawing upon this neo-Kantian approach to scientific models, the book provides a novel metaphysical account of what psychiatric diagnoses are and novel epistemological guidelines for constructing psychiatric diagnoses. Psychiatric diagnoses are portrayed as models which abstract away from particular aspects of particular people to create generalised models that are applicable to multiple people. In Defence of Psychiatric Diagnoses is essential reading for all scholars and researchers of the philosophy of science especially those focussing on the philosophy of psychiatry. Sam Fellowes is an Associate Lecturer in the Department of Philosophy, Politics and Religion at the University of Lancaster, UK.s
Chapter 1: Introduction -- Chapter 2: Psychiatry and the Philosophy of Psychiatry -- Chapter 3: Neo-Kantianism -- Chapter 4: Neo-Kantian understanding of symptoms -- Chapter 5: Neo-Kantianism and scientific entities -- Chapter 6: Neo-Kantianism and causes -- Chapter 7: Individual people -- Chapter 8: Conclusion.
Keywords: Medicine -- Philosophy; Science -- Philosophy; Psychiatry; Philosophy of Medicine; Philosophy of Science; Psychiatry